Toward a chemical reanalysis in a coupled chemistry‐climate model: An evaluation of MOPITT CO assimilation and its impact on tropospheric composition. Issue 12 (18th June 2016) - Gaubert, B.; Arellano, A. F.; Barré, J.; Worden, H. M.; Emmons, L. K.; Tilmes, S.; Buchholz, R. R.; Vitt, F.; Raeder, K.; Collins, N.; Anderson, J. L.; Wiedinmyer, C.; et al.
Abstract: We examine in detail a 1 year global reanalysis of carbon monoxide (CO) that is based on joint assimilation of conventional meteorological observations and Measurement of Pollution in The Troposphere (MOPITT) multispectral CO retrievals in the Community Earth System Model (CESM). Our focus is to assess the impact to the chemical system when CO distribution is constrained in a coupled full chemistry‐climate model like CESM. To do this, we first evaluate the joint reanalysis (MOPITT Reanalysis) against four sets of independent observations and compare its performance against a reanalysis with no MOPITT assimilation (Control Run). We then investigate the CO burden and chemical response with the aid of tagged sectoral CO tracers. We estimate the total tropospheric CO burden in 2002 (from ensemble mean and spread) to be 371 ± 12% Tg for MOPITT Reanalysis and 291 ± 9% Tg for Control Run. Our multispecies analysis of this difference suggests that (a) direct emissions of CO and hydrocarbons are too low in the inventory used in this study and (b) chemical oxidation, transport, and deposition processes are not accurately and consistently represented in the model. Increases in CO led to net reduction of OH and subsequent longer lifetime of CH4 (Control Run: 8.7 years versus MOPITT Reanalysis: 9.3 years). Yet at the same time, this increase led to 5–10% enhancement of Northern Hemisphere O3 and overall photochemical activity via HO x recycling. Such nonlinear effects further complicate the attribution to uncertainties in direct emissions alone. This has implications to chemistry‐climate modeling and inversion studies of longer‐lived species. Key Points: A full year of global reanalysis of CO is evaluated and investigated Assimilation reveals larger role of hydrocarbon oxidation in the CO burden Model CH4 lifetime improvement with CO reanalysis points to uncertainties in nonlinear processes